THE QUALITY OF LIBRARY SERVICE AT THE BALAI DIKLAT KEAGAMAAN SURABAYA - Mustofa, Aqila Nadia; Nabila, Zulfa Naura; Sofiyani, Zulfatun (IQRA`: Jurnal Perpustakaan dan Informasi, 2025)
This study aims to evaluate the quality of services at the Religious Training Center Library in Surabaya. The method used is a qualitative approach, with data collection through in-depth interviews and direct surveys of library visitors. The results indicate that human resources, particularly the competence of librarians, significantly impact the quality of services provided. Trained and experienced librarians are capable of delivering accurate and relevant information, as well as assisting users in the information search process. Although most users express satisfaction with the services offered, there are several aspects that need improvement, especially regarding the speed of the borrowing and returning processes. Users have noted that long wait times to obtain desired books can diminish satisfaction levels, particularly for those with limited time. This study recommends enhancing training for librarians and developing user education programs to optimize library facility utilization.Keyword: Service quality, library, librarian, user satisfaction, user education, Surabaya.